2020
DOI: 10.1111/jch.13764
|View full text |Cite
|
Sign up to set email alerts
|

Rationale, design, and baseline characteristics of the Cardiovascular Prognostic COUPLING Study in Japan (the COUPLING Registry)

Abstract: Vascular biomarkers, including the cardio-ankle vascular index (CAVI), are increasingly being recognized as important indicators of cardiovascular risk. CAVI has been shown to have good discriminative ability for detecting new-onset hypertension, but results of studies investigating cardiovascular risk prediction are inconsistent.Furthermore, there is a lack of data on the prognostic value of changes in CAVI over time. The Cardiovascular Prognostic Coupling study was designed to determine the impact of baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 34 publications
(43 reference statements)
1
12
0
2
Order By: Relevance
“…The HOPE Asia Network has published a number of papers on important Asia‐specific topics in hypertension . This Asia‐specific issue of the Journal of Clinical Hypertension provides an important resource including original research and review articles on the management of hypertension from a variety of Asian viewpoints, including topics such as central BP, environmental factors, comorbidities such as diabetes, atrial fibrillation, heart failure, and dementia, recent Asian guidelines and so forth . This issue also includes reports from twelve countries/regions in Asia to help define and highlight the current status of hypertension, its management, and their initiatives.…”
Section: Resultsmentioning
confidence: 99%
“…The HOPE Asia Network has published a number of papers on important Asia‐specific topics in hypertension . This Asia‐specific issue of the Journal of Clinical Hypertension provides an important resource including original research and review articles on the management of hypertension from a variety of Asian viewpoints, including topics such as central BP, environmental factors, comorbidities such as diabetes, atrial fibrillation, heart failure, and dementia, recent Asian guidelines and so forth . This issue also includes reports from twelve countries/regions in Asia to help define and highlight the current status of hypertension, its management, and their initiatives.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it has been reported that CAVI ≥ 9.0 predicted higher cardiovascular events in diabetic patients (34). On the other hand, the associations between changes of CAVI and prognosis have not yet been examined (35). A prospective, large-scale, and longitudinal study with repeated measurement of CAVI in high cardiovascular risk patients, the Coupling registry, has been under way (35).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the associations between changes of CAVI and prognosis have not yet been examined (35). A prospective, large-scale, and longitudinal study with repeated measurement of CAVI in high cardiovascular risk patients, the Coupling registry, has been under way (35). The study may provide useful information on the significance of both baseline CAVI and changes in CAVI over time as indicators of cardiovascular prognosis (35).…”
Section: Discussionmentioning
confidence: 99%
“…The results of our single‐arm study did not show any favorable effect of luseogliflozin on arterial stiffness, measured using the cardio‐ankle vascular index (CAVI) 2 . As a measure of arterial stiffness, CAVI is relatively independent of blood pressure (BP) and is now widely used in cardiovascular research and clinical practice 3–7 …”
mentioning
confidence: 85%
“…2 As a measure of arterial stiffness, CAVI is relatively independent of blood pressure (BP) and is now widely used in cardiovascular research and clinical practice. [3][4][5][6][7] SGLT 2 inhibitors were primarily developed as antidiabetic agents, but are also considered as a new class of "antihypertensive drugs" due to their homeostatic mechanisms. These include regulation of body fluid volume by diuretic activity and attenuation of sympathetic nerve-mediated salt sensitivity, which may be closely associated with the cardiorenal protective properties.…”
Section: E T T E R T O T H E E D I T O R -R E S P O N S Ementioning
confidence: 99%